Endoprótese customizada para o tratamento de aneurismas complexos aorto-ilíacos - Reis Neto, Fernando (2024)
Introduction: Even though estimates vary; a 20 to 40% failure rate for endovascular treatment of aortic and iliac aneurysms is seen. Objective: We evaluated the initial results of customized fenestrated and branched endovascular repair of complex aortoiliac aneurysms with a national device in the Brazilian public health system. We compared them with the main studies in the literature. Method: Twenty-three patients treated in a prospective, consecutive, nonrandomized, single-center study between July 2021 and August 2024 were analyzed. The patients were divided into two groups: Group 1- justarrenal, pararenal, suprarenal and thoracoabdominal aortic aneurysms; Group 2- iliac aneurysms with the use of an iliac branch device group. The primary outcome included mortality, type 1 or 3 endoleak, and a 30-day reintervention-free rate. Descriptive statistical analysis, Wilcoxon test (u=.05), Kaplan-Meier and ROC curves and chi-square test were applied Results In Group 1, fourteen patients were treated with custom-made endoprostheses. 78.5% (11) males, mean age 70.29 + 11.53 years, aneurysm diameter 70.77 + 18.34 mm underwent custom fenestrated/branched device (F/BEVAR). The aneurysms were divided into 64% complex abdominal aneurysms; 14.2% type II thoracoabdominal aneurysm with aortic dissection, 7.1% type thoracoabdominal aneurysm, 7.1% type III thoracoabdominal aneurysm and 7.1% penetrating ulcer of the aortic arch. In Group 2, nine patients, all male, were treated with a customized iliac branching device. Patients mean age 70.56 + 3.53 years, common iliac aneurysm diameter 39,58 +5,72mm, being treated Isolated in three cases (33%) and associated with aortic aneurysm in six cases (67%). The F/BEVAR technique included the renal and visceral arteries, and the iliac branch group included the internal iliac arteries. Technical success was achieved in all cases. One-year survival was 92.8% in Group 1 and 89% in Group 2; as one patient died from complications of gastric cancer. No case required early reintervention. Adverse events greater than 30 days included in group 1: one death in group 1 (7.1%), two spinal cord ischemia in group 1 (14.2%), three acute kidney injuries (21.3%) and one amputation greater transtibial (7.1%). In group 2, no deaths within 30 days, and presented: one decompensated heart failure (11%), one intraoperative vascular access bleeding (11%), and one nosocomial pneumonia (11%). Conclusions: The endovascular treatment of complex aneurysms with the customized Apolo? Nano Endoluminal endoprosthesis has proven to be safe and effective when performed in a high-volume center of the Brazilian Unified Health System. The good early patency of the vessels and the low initial mortality, given the complexity of the cases, can support the continuing study and expansion of this device for use in the treatment of complex aortic aneurysms.